Changes over time in the management of long‐term conditions in primary health care for adults with intellectual disabilities, and the healthcare inequality gap. Issue 2 (30th November 2020) - Hughes‐McCormack, Laura; Greenlaw, Nicola; McSkimming, Paula; McCowan, Colin; Ross, Kevin; Allan, Linda; Henderson, Angela; Melville, Craig; Morrison, Jill; Cooper, Sally‐Ann
Abstract: Background: Quality of primary healthcare impacts on health outcomes. This study aimed to quantify trends in good practice and the healthcare inequalities gap. Method: Indicators of best‐practice management of long‐term conditions and health promotion were extracted from primary healthcare records on 721 adults with intellectual disabilities in 2007–2010, and 3638 in 2014. They were compared over time, and with the general population in 2014, using Fisher's Exact test and ordinal regression. Results: Management improved for adults with intellectual disabilities over time (OR = 5.32; CI = 2.69–10.55), but not for the general population (OR = 0.74; CI = 0.34–1.64). However, it remained poorer, but to a lesser extent, compared with the general population (OR = 0.38; CI = 0.20–0.73 in 2014, and OR = 0.05; CI = 0.02–0.12 in 2007–2010). In 2014, health care was comparable to the general population on 49/78 (62.8%) indicators. Conclusions: The extent of the healthcare inequality gap reduced over this period, but remaining inequalities highlight that further action is still necessary.